The Oman Border Fence Project 2021: A Journey through the Hydraulic, Agricultural and Funerary Landscapes of al-ʿAyn - Sheehan, Peter; Khalifa, Mohammed; Al Ajou, Malak; Al Marzooqi, Nour; van Bellegem, Maickel; Ferreira, Anabela; Al Merri, Jaber; Power, Timothy; Benoist, Anne; Purdue, Louise; et al. (Proceedings of the Seminar for Arabian Studies, 2023)
Over a six-month period from January to August 2021 the Historic Environment Department of DCT Abu Dhabi carried out archaeological monitoring and excavation along an 11.5km stretch of a project to renew the existing border fence between UAE and Oman. The project produced a wealth of new data on the development of the historic oasis landscape of al-ʿAyn. Some of the most significant features include a monumental stone tomb, an apparently extensive Iron Age cemetery and high-status tombs of Late Pre-Islamic (PIR) date. Along with this funerary landscape we have identified more than 50 ancient aflaj or underground water channels of various dates and techniques of construction, along withextensive evidence for distinct phases of Iron Age agriculture and the organization of their associated irrigation systems and agricultural plots. This paper will provide an overview of the nature and progress of the fieldwork and initial study of the finds associated with the various feature groups, including a corpus of Iron Age and PIR ceramics from both funerary and agricultural contexts, a large number of chlorite vessels, PIR iron weaponry, extensive environmental samples and information on the geology and wādī systems shaping this cultural landscape.